Параметры поверхностных акустических волн в пьезокристаллах при высоких значениях температуры - Dvoesherstov, M. Yu.; Cherednick, V. I. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
In the design of high-temperature SAW sensors, the task arises of calculating the propagation characteristics of surface acoustic waves and determining their optimal orientations in piezocrystalline materials. This work examines the influence of temperature on the main characteristics of SAW propagation in piezocrystals at elevated temperatures and provides recommendations on the use of piezocrystalline substrates such as quartz, lithium niobate, lithium tantalate, gallium orthophosphate, and langasite as SAW waveguides.